Trifoliate Orange Seed Germination Enhancing Method in Mid Hill of Nepal - Acharya, Umesh K.; Pakka, Roshan (Journal of Nepal Agricultural Research Council, 2019)
Trifoliate orange seedlings are used as rootstock for citrus crops due to cold hardiness and phytopthora disease tolerance. Nursery owners usually prepare raised bed in open field to sow seeds of trifoliate. The trifoliate seed production in government farms are very low compared to its demand due to limited number of fruiting trees. Further the germination percent in open nurseries are very low. Hence, production of grafted sapling is very much affected by unavailability of rootstock. Therefore, a study was carried out in National Citrus Research Program, Dhankuta to increase germination rate of trifoliate orange in the year 2016 and 2017. Trifoliate seeds were extracted from three stages of fruits (green mature, half yellow and full yellow) and sown at three dates (September 1st week, September 3rd week and October 1st week) at three raised bed (open field, 50-cm low plastic tunnel with or without sides open). The data on percentage seed germination was taken at 35, 50, 65, 90 and 210 days after seed sowing. The fruit maturity had no effect on germination percentage irrespective of sowing date and method of beds used. The date of sowing resulted significantly higher germination at earlier days but there was non-significant effect during final germination count. Plastic tunnel with open sides resulted 80% germination compared to 46% in tunnel side closed nursery. Hence, low plastic tunnel raised bed having open sides is the best option to raise trifoliate seed sown during 1st week of September to 1st week of October in agro-climatic conditions like Dhankuta.